Reasoning web. semantic technologies for advanced query answering 8th International Summer School 2012, Vienna, Austria, September 3-8, 2012. Proceedings - Krennwallner, Thomas; Eiter, Thomas (Lecture Notes in Computer Science, 2012)
This volume contains the lecture notes of the 8th Reasoning Web Summer School 2012, held in Vienna, Austria, in September 2012, in the form of worked out tutorial papers on the various topics that have been covered in that school. The 2012 summer school program had been put together under the general leitmotif of advanced query answering topics for the Web. The idea was to address on the one hand foundations and computational aspects of query answering, in formalisms, methods and technology, and on the other hand to also spotlight some rising or emerging application fields relating to the Semantic Web in which query answering plays a role, and which by their nature also pose new challenges and problems for this task; linked stream processing, geospatial data, semantic wikis, and argumentation on the web fall in this category.